P3.209 Low Rates of STI Co Infection Observed in HIV Positive Women Participating in an HPV Vaccine Study In Canada. (13th July 2013) - Moses, E; Blitz, S; Raboud, J; Singer, J; Loutfy, M; Smaill, F; Walmsley, S; Money, D
Abstract : Background: HIV positive women with sexually transmitted infections (STIs) face increased reproductive health risks and negative health outcomes. This sub-analysis was performed to determine the co-factors associated with a history of STI's in this high-risk population. Methods: Data was collected as part of an ongoing multi-centred study of the immunogenicity and safety of a quadrivalent HPV vaccine in HIV+ women in Canada, Clinical data, along with genital HPV-DNA sampling and liquid based cervical cytology data, was collected 3 months prior to initial vaccination. Results: Of the 255 sexually active women in this sub-analysis, characteristics were: mean age of 37, ethnicity: black 42%, white 36%, aboriginal 11% and other 10%. Mean number of lifetime sexual partners 5 (3–15), 70% of women were sexually active within the last year, 18% with a new partner. Condom use with sexual intercourse was reported at 37% every time, 26% sometimes and 37% never. 63.5% of women reported ever having an STI. Specifically; herpes 31%, condylomas 29%, chlamydia 22%, gonorrhoea 15%, trichomonas 13% and syphilis 9%. Multivariable logistic regression was used to determine predictors associated with history of an STI. Compared to black women, white women (OR = 2.4, p < 0.02) and aboriginal women (OR = 7.9, p < 0.01) were more likely to report an STI. Older women were less likely (OR = 0.5/5 years, p = 0.02) and women who had been sexually active for longer were more likely to report an STI (OR = 2.5, p = 0.001). Conclusion: A reported history of STI infection was notably higher in aboriginal and white women compared to black women. Younger women and those with more years of sexual activity were also more likely to report a prior STI. Despite a substantive history of STI's once engaged in HIV care a significantly lower incidence of concurrent active STI's was observed in this population of women.